Organizational Characteristics and Employee Overall Satisfaction: A Comparison of State-Owned and Non State- Owned Enterprises in Vietnam - Nguyen, Lam D. (The South East Asian Journal of Management, 2011)
Differences in employee overall job satisfaction between public and private sector organizations have long been a topic of organizational academic debate. This study looks at the differences and the relationships between organizational characteristics and employee overall satisfaction between the State-Owned Enterprises (SOEs) and the Non-State-Owned Enterprises (Non-SOEs) in Vietnam. The purpose of this study is threefold: 1) to examine the differences in organizational characteristics in 7 components including purposes, structure, leadership, relationships, rewards, helpful mechanisms, and attitude toward change; 2) to examine the differences in employee overall satisfaction; and 3) to explore the relationship between organizational characteristics and employee overall satisfaction between the two sectors. The sample includes 20 SOEs and 20 Non-SOEs with a total of 860 employees. The findings empirically reinforce existing organization behavior literature: employee satisfaction is to some extent shaped by the settings of their organizations. Limitations and future research opportunities are also identified.